QUALITY INDICATORS OF BLUE-COLORED PROGENY OBTAINED FROM MATING DIFFERENT GENOTYPES (Modern American Journal of Biological and Environmental Sciences, 2025)
This article presents the results of biometrical analysis and draws conclusions about the flower types and grades of blue karakul lambs, as well as the dependence of these indicators on color evenness.